Three Paths to Particle Dark Matter - Lee, Samuel Kuhnman (California Institute of Technology, 2012)
In this thesis, we explore examples of each of the three primary strategies for the detection of particle dark matter: indirect detection, direct detection, and collider production.

We first examine the indirect detection of weakly interacting massive particle (WIMP) dark matter via the gamma-ray photons produced by astrophysical WIMP annihilation. Such photons may be observed by the Fermi Gamma-ray Space Telescope. We propose the gamma-ray-flux probability distribution function (PDF) as a probe of the Galactic halo substructure predicted to exist by N-body simulations. The PDF is calculated for a phenomenological model of halo substructure; it is shown that the PDF may allow a statistical detection of substructure.

Next, we consider the direct detection of WIMPs. We explore the ability of directional nuclear-recoil detectors to constrain the local velocity distribution of WIMP dark matter by performing Bayesian parameter estimation on simulated recoil-event data sets. We discuss in detail how directional information, when combined with measurements of the recoil-energy spectrum, helps break degeneracies in the velocity-distribution parameters. Considering the possibility that velocity structures such as cold tidal streams or a dark disk may also be present in addition to the Galactic halo, we discuss the potential of upcoming experiments to probe such structures.

We then study the collider production of light gravitino dark matter. Light gravitino production results in spectacular signals, including di-photons, delayed photons, kinked charged tracks, and heavy metastable charged particles. We find that observable numbers of light-gravitino events may be found in future collider data sets. Remarkably, this data is also well suited to distinguish between scenarios with light gravitino dark matter, with striking implications for early-Universe cosmology.

Finally, we investigate the related matter of radiative corrections to the decay rate of charged fermions caused by the presence of a thermal bath of photons. The cancellation of finite-temperature infrared divergences in the decay rate is described in detail. Temperature-dependent radiative corrections to the two-body decay of a hypothetical charged fermion and to electroweak decays of a muon are given. We touch upon possible implications of these results for charged particles in the early Universe.
Keywords: Astrophysics; directional detection of dark matter; finite-temperature field theory; particle dark matter; dark-matter annihilation; gravitinos